Collective Structural Relaxation in Phase‐Change Memory Devices. (16th July 2018) - Le Gallo, Manuel; Krebs, Daniel; Zipoli, Federico; Salinga, Martin; Sebastian, Abu
Abstract: Phase‐change memory devices are expected to play a key role in future computing systems as both memory and computing elements. A key challenge in this respect is the temporal evolution of the resistance levels commonly referred to as "resistance drift." In this paper, a comprehensive description of resistance drift as a result of spontaneous structural relaxation of the amorphous phase‐change material toward an energetically more favorable ideal glass state is presented. Molecular dynamics simulations provide insights into the microscopic origin of the structural relaxation. Based on those insights, a collective relaxation model is proposed to capture the kinetics of structural relaxation. By linking the physical material parameters governing electrical transport to such a description of structural relaxation, an integrated drift model that is able to predict the current–voltage characteristics at any instance in time even during nontrivial temperature treatments is obtained. Accurate quantitative matching with experimental drift measurements over a wide range of time (10 decades) and temperature (160–420 K) is demonstrated. Abstract : A key challenge for integrating phase‐change memory in future computing systems is the temporal evolution of the resistance levels ("resistance drift"). This paper presents a collective relaxation model to describe resistance drift resulting from spontaneous structural relaxation of the amorphous phase‐change material. Quantitative matching with experimental drift measurements over 10 decades of time and 160‐420 K temperature range is demonstrated.